PENGARUH CURRENT RATIO, EARNING PER SHARE, DEBT TO EQUITY RATIO DAN UKURAN PERUSAHAAN TERHADAP HARGA SAHAM PADA PERUSAHAAN LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2021-2024 - Falki; Gustia Harini; Nora Susanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of Current Ratio (CR), Earnings Per Share (EPS), Debt to Equity Ratio (DER), and Firm Size on Stock Prices of LQ45 companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. This research employs a quantitative approach using secondary data in the form of annual financial statements and closing stock prices. The sample was determined through purposive sampling technique. The data were analyzed using panel data regression, with model selection conducted through the Chow test, Hausman test, and Lagrange Multiplier test. The results indicate that partially, Earnings Per Share has a significant effect on stock prices, while Current Ratio, Debt to Equity Ratio, and Firm Size do not entirely show significant effects. However, simultaneously, CR, EPS, DER, and Firm Size have a significant effect on stock prices. These findings support signaling theory, which suggests that financial information serves as a signal to investors in making investment decisions. This study is expected to provide insights for investors in evaluating company performance before investing in stocks